ANALYSIS OF THE APPLICATION OF CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) ON THE USE OF CLEAN WATER IN THE COMMUNITY IN MEUTARA VILLAGE, JAYA SUB-DISTRICT, ACEH JAYA DISTRICT - Karma, Taufiq; Zikra, Safaratul (Transpublika Publisher, 2024)
Clean and Healthy Living Behavior (PHBS) refers to the practice of maintaining personal cleanliness and health awareness in daily life. According to the World Health Organization (WHO), clean water is defined as water that meets health standards and is safe for daily use, including consumption, drinking, and food preparation. Adopting healthy living practices is crucial for everyone, as it offers numerous benefits, including improved mental and physical health, increased focus, family welfare, and the creation of a pleasant and peaceful living environment. Water plays a vital role in sustaining life, and it is essential for individuals to secure an adequate supply. However, the water used is often not compliant with health standards, frequently containing germs or harmful substances that pose a threat to human health. PHBS encompasses all health behaviors performed with conscious awareness, enabling individuals to manage their health effectively and participate actively in health-related activities. Therefore, it is important to disseminate information about PHBS to the community to raise awareness of its significance. This awareness can foster the adoption of PHBS practices, ultimately enhancing the health and welfare of family members and the community at large.